Anlotinib: A Novel Targeted Drug for Bone and Soft Tissue Sarcoma - Li, Shenglong (Frontiers in Oncology, 2021)
Bone and soft tissue sarcoma accounts for about 15% of pediatric solid malignant tumors and 1% of adult solid malignant tumors. There are over 100 subtypes of sarcomas, each of which is notably heterogeneous and manifested by remarkable phenotypic and morphological variability. Anlotinib (AL3818) is a novel oral tyrosine kinase inhibitor (TKI) targeting c-kit, platelet-derived growth factor receptors, fibroblast growth factor receptor and vascular endothelial growth factor receptor. In comparison with the placebo, anlotinib was associated with better overall survival (OS) and progression-free survival (PFS) in a phase III trial of patients with advanced non-small cell lung cancer (NSCLC), albeit with cancer progression post two lines of previous treatments. Recently, the National Medical Products Administration approved anlotinib monotherapy as a third-line treatment for advanced NSCLC patients. Additionally, a phase IIB randomized trial substantiated that anlotinib was associated with significant longer median PFS in patients with advanced soft tissue sarcoma (STS). Moreover, anlotinib was also effective in patients with advanced medullary thyroid carcinoma and metastatic renal cell carcinoma (mRCC). Anlotinib has similar tolerability to other TKIs targeting VEGFR and other tyrosine kinase-mediated pathways. However, anlotinib has a notably lower rate of side effects ≥ grade 3 relative to sunitinib. This review discussed the remarkable characteristics and major dilemmas of anlotinib as the targeted therapy for sarcomas.